Greetings From the Editor - İlker YAĞCI (Archives of Rheumatology, 2018)
The June issue of the Archives of Rheumatology comprises a number of essential highlights among many other papers. The first is expert opinions about the management of psoriatic arthritis (PsA), which was prepared by the Turkish League Against Rheumatism (TLAR).(1) The article includes recommendations and will help improve outcomes for patients with PsA. You will also find an original article by Tiraje TUNCER on the prevalence of rheumatoid arthritis (RA) and spondyloarthritis (SpA) in Turkey. This is the first nationwide epidemiological study to estimate the prevalence of RA and SpA in Turkey.(2) The June issue also consists two experimental studies that investigate effects of ozone and bee venom and hesperidin on induced arthritis in rats.(3,4) The study of Kim and Choe evaluated the effects of passive smoking on disease activity in patients with RA, and they have found that the passive smokers had higher disease activity.(5) There are also essential articles about RA, fibromyalgia, lupus, juvenile idiopathic arthritis, and connective tissue disease- associated interstitial lung disease. I hope all articles will make crucial contributions to the literature. The editorial team of the Archives of Rheumatology has changed in May 2018. My predecessor Levent ÖZÇAKAR handled the manuscripts of the June issue. I would like to thank him for his vision and significant efforts for the improvement of the journal. I would also like to thank previous associate editors Ke-Vin CHANG, Marija JELUŠIĆ-DRAŽIĆ, Murat KARA, Ming-Chi LU, Meltem ALKAN MELİKOĞLU, Porin PERIĆ, Croatia Fausto SALAFFI and Timur EKİZ. They did a great job in moving this journal forward and making it an important source of reference in daily rheumatology practice. As the new editorial team, we will work to carry the journal even further on this path and hopefully enhance its influence both nationwide and internationally. Sincerely